El “respeto a la diversidad” en la escuela: atolladeros del relativismo cultural como principio moral - Batallán, Graciela; Campanini, Silvana (Revista de Antropología Social, 2007)
“Respect for diversity” included in normative and curricular texts on Argentinean educative system represent an opportunity to reflect about cultural relativism in its potential for criticism and its limits as a moral principle. This article analyzes the uses of precepts that emerge at schools as a product of a contradictory bond between contemporary democratic principles for the institution and conceptual frames about social life and learning. Also, this article aims to relocate relativism’s analytic capacity as a tool against ethnocentrism, both in order to both elaborate the inherent conflict on school’s practices and also as a cultural critique –sensitive to that institution’s specific logic–.